(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Intramedullary nailing of long bone fractures have been associated with fat embolism and thermal necrosis due to reaming.1,2 An attempt to reduce the incidence of these complications Reamer-Irrigation-Aspiration(RIA) system was developed (Synthes, Paoli, PA, USA).This innovative system provides simultaneous continuous irrigation and suction while reaming long bones. The marrow contents, bone fragments and irrigation fluid is passed through a filter first and then into a suction bag. The second generation RIA system was launched in 2019 (Fig. I). It has new design for easy handling, small reamer head size of 10 mm (first generation RIA system has 12 mm reamer head size) and has larger holes for improved irrigation and suction. The design and characteristics of this reamer are different from standard reamer and detailed guidelines of RIA technique and usage has already been established.3 The purpose of this editorial is to update the Orthopaedic community of Pakistan about the expanded indications, safety and efficacy of RIA system. The indications of RIA have been expanded recently. It has been used for treating post operative osteomyelitis,4 non unions of long bone 5-9 and for obtaining mesenchymal stem cells.10 Zalavras4 treated 8 tibial osteomyelitis and 3 femur osteomyelitis with debridement of the medullary canals utilizing RIA system and reported no infection at six months follow up.